Utilization of actigraphy to assess undiagnosed sleep disturbances among healthy adults in home-based settings - Mohamad Noor, Zaswiza; Smith, Alesha; Smith, Simon; Nissen, Lisa M. (2012)
Introduction: Normal sleep duration and sleep/wake patterns can vary markedly by individual, culture and lifestyle. Many people believe they have normal and quality sleep, however they may display undiagnosed sleep disturbances. Early detection can improve the condition and may prevent future long-term use of sleep medications. Sleep assessment and monitoring are therefore vital, thus an appropriate validated measuring tool is essential to assess sleep quality and quantity in a home-based setting. Aim: This study aims to identify undiagnosed sleep disturbances in healthy adults using actigraphy. Methods: Individuals with no history of sleep-related problems were invited and informed about the study prior to providing informed consent. Each participant was provided with an actigraph (similar to a wrist watch) to be worn for 24-hours/day for seven consecutive days to record the sleep/wake patterns. At the end of the duration, the researcher downloaded the actigraph data using SleepConsultant™ software to generate an easy to interpret sleep report and participants completed a set of questionnaires. Results: Acceptability of the actigraphy was supported unanimously by all participants. Only 43.8% subjects achieved the normal range (7-9 hours) of Total Sleep Time (TST), and surprisingly 75% of them had an average of Sleep Efficiency (SE%) below the normal rate (normal rate SE% value >85%). Discussion: Utilization of actigraphy to assess sleep/wake patterns in healthy adults is possible to gain early detection of sleep disturbances before the condition worsens. Community pharmacies could use actigraphy to implement future interventions/services to improve sleep-related problems in primary care.